2019
DOI: 10.3390/sports7070175
|View full text |Cite
|
Sign up to set email alerts
|

Inter- and Intra-Individual Differences in EMG and MMG during Maximal, Bilateral, Dynamic Leg Extensions

Abstract: The purpose of this study was to compare the composite, inter-individual, and intra-individual differences in the patterns of responses for electromyographic (EMG) and mechanomyographic (MMG) amplitude (AMP) and mean power frequency (MPF) during fatiguing, maximal, bilateral, and isokinetic leg extension muscle actions. Thirteen recreationally active men (age = 21.7 ± 2.6 years; body mass = 79.8 ± 11.5 kg; height = 174.2 ± 12.7 cm) performed maximal, bilateral leg extensions at 180°·s−1 until the torque values… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
32
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(36 citation statements)
references
References 59 publications
4
32
0
Order By: Relevance
“…Specifically, Anders et al[ 7 ] characterized bilateral fatigue by decreased muscle fiber action potential conduction velocity (EMG MPF) and motor unit recruitment (MMG AMP), as well as no change in muscle excitation (EMG AMP) and motor unit firing rate (MMG MPF). Thus, the findings of previous studies[ 4 - 6 , 11 ] suggested BL and UL muscle actions exhibit distinct patterns of neuromuscular fatigue.…”
Section: Introductionmentioning
confidence: 71%
“…Specifically, Anders et al[ 7 ] characterized bilateral fatigue by decreased muscle fiber action potential conduction velocity (EMG MPF) and motor unit recruitment (MMG AMP), as well as no change in muscle excitation (EMG AMP) and motor unit firing rate (MMG MPF). Thus, the findings of previous studies[ 4 - 6 , 11 ] suggested BL and UL muscle actions exhibit distinct patterns of neuromuscular fatigue.…”
Section: Introductionmentioning
confidence: 71%
“…Hence, we place sEMG sensors on the four muscles. The patterns of lower limb responses during dynamic muscle actions are with no differences [16]. To collect massive amounts of training data, the sEMG sensors were placed on both limbs in the data in the data collection process.…”
Section: ) Experimental Protocolmentioning
confidence: 99%
“…Indeed, MMG signal represents the mechanical manifestation of muscle activity [ 7 ] and further indicates the neurophysiology reflected by the mechanical counterpart to the electrical activity of unfused active motor units [ 5 ]. Attempts made in the assessment of crosstalk [ 8 ], quantification [ 9 ], and applications in assistive technology [ 10 ] support MMG signal as an alternative to EMG signal for the screening of muscle function [ 11 ], in terms of fatigue [ 12 ], muscle force [ 13 ], and its derivative (torque) [ 14 ] as well as for prosthesis control [ 15 ] and the detection of myopathies [ 16 ].…”
Section: Introductionmentioning
confidence: 99%